Anti-obesity and body weight reducing effect of Docynia indica (Wall.) Decne fruit extract fractions in experimentally obese mice - Loan, Nguyen Thi Thanh; Tan, Hoang Thi Minh; Tam, Vu Thi Hanh; Luan, Chu Luong; Huong, Le Mai; Lien, Do Ngoc (VNU Journal of Science: Natural Sciences and Technology; Vol 27 No 2, 2011)
Abstract . The objective of the present study was to assess anti-obesity and body weight reducing effect of Docynia indica (W.) Decne fruit extract fractions base on experimentally obese mice model.        Male mice ( Mus musculus , Swiss strain of 4 weeks of  age, weighed at 14-15g) purchased from National Institute of Hygiene and Epidemiology (NIHE) were  housed in a temperature (25 ± 2 0 C) and humidity (80% ± 10 %) under a 12h light/12 h dark cycle. Diets and tap water were provided ad libitum. Experimental mice were divided into 5 groups in which, the first group was fed with normal pellet diet (ND) (Standard chow from NIHE), and other groups were fed high fat diet (HFD) containing 58% calories as fat for a period of 28 days [1,2] The obese mice were treated daily with extract fractions from Docynia indica fruit for 14 days The HFD mice exhibited significant increase in body weight to be 44.4% as compared to ND group at that time (p ≤ 0.05). Besides, the HFD mice showed significant increase in blood lipid parameters such as total cholesterol(TC),  triacylglycerols(TG), Low Density Lipoprotein cholesterol (LDL-c) and glucose concentrations to be 67.3%, 46.2 %, 28.6 % and 18.3 %, respectively as compared to ND mice. Our investigations show that anti-obesity and body weight reducing effects in obese mice treated orally daily with 650 mg/kg of extract fractions from  Docynia indica (W.) Decne fruit were demonstrated. The obtained results indicate that the body weights of HFD mice daily treated by different extract fractions were reduced by 9.5 % (for ethyl acetate extract), 3.8 % (for chloroform extract) and 8.9 % (for total ethanol extract) as compared to the control( obese mice untreated )(p ≤ 0.05)). Besides,the blood lipid parameters of HFD mice treated with ethylacetae extract fraction of Docynia indica fruits for 14 days were decreased clearly, such as TC decreased 10.3%,TG decreased 31.6% LDL-c decreased 28.6%, especially blood glucose level in obese mice decreased 14.3% compared to control (p≤ 0.05). Keywords: Anti-obesity, body weight reducing effect, Docynia indica (W.) Decne, experimentally obese mice.